Penerapan Expressive Writing Pada Mahasiswa Yang Menyelesaikan Tugas Akhir Dengan Tingkat Stres Di Universitas ‘Aisyiyah Surakarta - Nur Ellisa Fitriani; Ida Nur Imamah (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Background: Final-year students are entrusted with the responsibility of completing their final assignments as a prerequisite for graduation and degree attainment. The prevalence of mental health problems among these students is higher, with more pronounced stress symptoms compared to new students. Central Java is ranked third, reporting 95,461 cases of emotional and mental disorders among individuals aged 15 and above. Expressive writing, which revolves around emotions, assists each student in channeling and expressing their anger through written words. Objective: Depicting students' stress levels through the implementation of expressive writing to reduce stress among those finalizing their Independent Study (KTI) at Universitas 'Aisyiyah Surakarta. Method: A case study approach is employed. A pretest utilizing the DASS-42 (Depression Anxiety Stress Scale) questionnaire determines respondents' stress levels. Following implementation, a posttest is conducted using the same scale. Results: Findings indicate moderate stress levels pre-implementation, which decrease to mild stress post-implementation. Conclusion: The application of expressive writing significantly influences the reduction of stress levels experienced by final-year students at Universitas 'Aisyiyah Surakarta.